Respostas
respondido por:
0
Resposta:
Três soluções (x, y): (0, 3), (2, 2) e (4, 1)
Explicação passo-a-passo:
.
. Três soluções de: x + 2y = 6
.
. x = 0 ....=> 2y = 6
. y = 6 ÷ 2....=> y = 3 (0, 3)
. x = 2.....=> 2 + 2y = 6
. 2y = 6 - 2
. 2y = 4
. y = 4 ÷ 2....=> y = 2 (2, 2)
. x = 4.....=> 4 + 2y = 6
. 2y = 6 - 4
. 2y = 2
. y = 2 ÷ 2....=> y = 1 (4, 1)
.
(Espero ter colaborado)
araujofranca:
Obrigado pela "MR".
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás